Counseling to Strength Religious Moderation In The Framework of Handling Religious And National Conflicts In Riau Province: PENYULUHAN PENGUATAN MODERASI BERAGAMA DALAM RANGKA MENANGGULANGI KONFLIK KEAGAMAAN DAN KONFLIK KEBANGSAAN DI PROVINSI RIAU - Azni; Irien Violinda Anggraini; Mutasir; Luqman Hakim Alhudry; Rian Vebrianto (Universitas Lancang Kuning, 2024)
Religious conflicts often occur in heterogeneous communities, including communities in Riau province. This paper aims to determine the results of community service carried out in the form of counseling on strengthening religious moderation in order to overcome religious conflicts and national conflicts in Riau Province. The community service carried out uses the PAR (Participation Action Research) method, which is a method for developing moderate attitudes and behaviors and promoting peace among religious leaders, community leaders, and youth in Riau Province, with 3 stages, namely planning, implementation and the reflection or evaluation stage. The results of this community service obtained that the implementation of this service was successfully carried out according to planning. Then, this service reflects a positive impact on the participants who attended the counseling, which further fosters the spirit of moderation in their religion, a steady spirit of tolerance and increasingly appreciates local wisdom and of course gets new knowledge that is useful in heterogeneous community for harmonious and peaceful life.